Socio-Demographic Profile, Morbidity Pattern and Reason for Elderly People Living in an Old Age Homes: A Community Based Study From Banke District - Shrestha, Merina; Chaudhary, Ram Chandra (Journal of Nepalgunj Medical College, 2019)
Background: Various aspects of socio-demographic conditions effect individual’s life at the time of an old age which ultimately make their life vulnerable and dependent on other people. Old age home is one of the important place for those elderly people whose spouse are not alive, have nuclear family background and no one at home to take care of them. Aims and objectives: To study socio-demographic profile, disease morbidity and factors effecting elderly people to live in an old age homes.Material and method: A community based cross sectional qualitative study was conducted among geriatric age group 65 and above, without any physical and mental severity, and living in old age homes in community field area of department of community medicine of Nepalganj medical college from 14th April2019 to 16th September 2019.The total sample size was 84.Results: Majority of female occupants (63.1%) belonged to age group 65 to 75 years old. Half of them were illiterate and their spouses were not alive (71.4%). Family member’s migration (63.1%) and nuclear family (67.9%) were the contributory factors for living in old age homes.Conclusion: The result of the study showed that there is need of geriatric social services and health facilities for making elderly people financially and emotionally strong.